2019
DOI: 10.1007/s13205-019-1792-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis of high- and low-oil Camellia oleifera reveals a coordinated mechanism for the regulation of upstream and downstream multigenes for high oleic acid accumulation

Abstract: Tea oil camellia (Camellia oleifera) is an important woody oil tree in southern China. However, little is known regarding the molecular mechanisms that contribute to high oleic acid accumulation in tea oil camellia. Herein, we measured the oil content and fatty acid compositions of high-and low-oil tea oil camellia seeds and investigated the global gene expression profiles by RNA-seq. The results showed that at the early, second and third seed developmental stages, a total of 64, 253, and 124 genes, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…Intriguingly, we also found that there was a trade-off relationship between the changes in diverse components, implying possible conversions of palmitic acid to stearic acid, SFAs to UFAs, and PUFAs to MUFAs during the accumulation of fatty acids. Past studies have proven that substantial variation in fatty acid composition is regulated by certain key pathways 60 , 61 . However, information regarding the metabolic mechanisms underlying fatty acid biosynthesis in C. oleifera on Hainan Island is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, we also found that there was a trade-off relationship between the changes in diverse components, implying possible conversions of palmitic acid to stearic acid, SFAs to UFAs, and PUFAs to MUFAs during the accumulation of fatty acids. Past studies have proven that substantial variation in fatty acid composition is regulated by certain key pathways 60 , 61 . However, information regarding the metabolic mechanisms underlying fatty acid biosynthesis in C. oleifera on Hainan Island is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG analysis showed that the results of XL106_1007 vs. XL106_0915 (early stage) and XL106_1007 vs. XL106_1022 (later stage) were similar and were mainly enriched in the pathway including energy metabolism, amino acid metabolism, fatty acid metabolism, carbohydrate metabolism, and biosynthesis of other secondary metabolites. These massively concentrated pathways have a great relationship with the synthesis of oil-tea Camellia [ 17 , 18 ]. In the two stages, the number of KEGG-enriched genes was 385 and 346, respectively, which indicated that a large number of the genes and pathways related to FA remained active in the pre- and poststage of XL106.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Peng et al [37] and Lin et al [38] used RNA-seq technology to study seeds development and lipid synthesis in different C. oleifera cultivars, which provide a new insight into the lipid biosynthesis and fatty acid accumulation mechanism. Wu et al [39] conducted a comparative transcriptome study on highoil and low-oil C. oleifera cultivars and found that the high expression of SAD accelerated oleic acid synthesis and accumulation and the low expression of FAD and FAE1 decreased the consumption of oleic acid for conversion. However, there are few comparative studies about seed development and lipid synthesis among different cultivars of C. oleifera.…”
Section: Introductionmentioning
confidence: 99%